Tuning the structures and electron transport properties of ultrathin Cu nanowires by size and bending stress using DFT and DFTB methods. Issue 29 (27th April 2015) - He, C.; Liu, G.; Zhang, W. X.; Shi, Z. Q.; Zhou, S. L.
<x xml:space="preserve">Abstract</x> Electron transport properties of ultrathin Cu nanowires with diameters of 0.2–1.0 nm under different bending stresses are reported, using density functional theory and density-functional-based tight-binding approaches, for application in flexible displays and solar cells.